An evaluation of the Crossover Youth Practice Model (CYPM): Recidivism outcomes for maltreated youth involved in the juvenile justice system. (June 2016) - Haight, Wendy; Bidwell, Laurel; Choi, Won Seok; Cho, Minhae
Abstract: This study examined youth recidivism (reoffending) outcomes of the Crossover Youth Practice Model (CYPM) in an urban county in a Midwestern state. Crossover youth are defined as maltreated youth who have engaged in delinquency. Decreased recidivism is one of the primary outcomes targeted by the CYPM. Previous internal, exploratory research on recidivism indicates positive outcomes for CYPM youth. In the current study, we used a quasi-experimental, post-test only design with independent historical and contemporaneous comparison samples. We linked state-level data from the State Court Information System with the Child Protection Administrative Data and the Automated Report Student System. Youth receiving CYPM services were less likely to recidivate than propensity score matched youth receiving "services as usual" even when controlling for location, time and other key covariates. Study limitations and implications are discussed. Highlights: Maltreated youths involved in delinquency have multiple developmental risks. The Crossover youth Practice Model targets youth outcomes in recidivism by providing earlier, more coordinated and individualized services. Youths receiving the CYPM were less likely to re-offend than propensity score matched youth.